CO2 saturated brine injected into fractured shale: An X-ray micro-tomography in-situ analysis at reservoir conditions. (November 2018) - Yu, Hongyan; Zhang, Yihuai; Lebedev, Maxim; Wang, Zhenliang; Ma, Jinfeng; Cui, Zhihao; Verrall, Michael; Squelch, Andrew; Iglauer, Stefan
Abstract: Fracture morphology and permeability are key factors in enhanced gas recovery (EOR) and Carbon Geo-storage (CCS) in shale gas reservoirs as they determine production and injection rates. However, the exact effect of CO2 -saturated (live) brine on shale fracture morphology, and how the permeability changes during live brine injection and exposure is only poorly understood. We thus imaged fractured shale samples before and after live brine injection in-situ at high resolution in 3D via X-ray micro-computed tomography. Clearly, the fractures' aperture and connectivity increased after live brine injection.